Th e Infl uence of Political Mythology on State Image - D. D. Polonskaya (Сравнительная политика)
Th roughout history, myth has always been an inherent part of any culture, as well as an instrument of socialization of any society’s representatives. Political myths play a specifi c role within the hole complex of myths as a part of political culture. To a great extent, the state image transforms due to the infl uence of the struggle between myths and counter-myths. Political image could not remain unchangeable in same manner as political myth is being modernized under the infl uence of changes in political culture.